COMPARISON OF TUBE THORACOSTOMY VS VATS IN THE MANAGEMENT OF EMPYEMA THORACIS IN FIBRINO-PURULENT STAGE IN CASES OF PNEUMONIA & CHEST TRAUMA - NAQVI , SMR; SHAH , SMA; MATEEN , A; FARHAN , IA (Biological and Clinical Sciences Research Journal, 2023)
Empyema thoracis has been considered a serious problem. Different treatment options are available for the management of empyema thoracis, and each of these procedures has its own merits and demerits. This study was designed to compare the outcome of Tube Thoracostomy and VATS in the fibrino-purulent stage of empyema due to pneumonia and chest trauma in terms of hospital stay and empyema resolution in the adult age group. Ninety patients in the study were randomly divided into two groups of equal numbers, i.e., 45 in each group, by lottery method. Patients in Group A underwent tube thoracostomy, and patients in Group B had VATS. Five days postoperatively, clinical examination and relevant investigations like CXR, USG Chest of all patients were done to find empyema resolution. The mean age, BMI, and duration of hospital stay of the patients in group A vs. B was 36±16.5 vs 28±11.4, 26.03±3.39 and 26.1±3.63 and 10±4.1 vs 5±1.24 respectively. In Group A vs. B, there were 96.7% vs. 80% males and 3.3% vs 20% females, respectively. Resolution of symptoms of empyema in group A vs. B was seen in 26.7% vs. 43.3% respectively (p=0.005). Short duration of hospital stay was seen in 15% vs. 48.3% of patients in Group A vs. B, respectively (p=0.000). The Fibrino-purulent stage of Empyema Thoracis, VATS, and Decortication led to early resolution compared to tube thoracostomy alone.